Influence of the inoculum source on the biohydrogen production - Vera-Toledo, Pedro (Universidad Autónoma de Tamaulipas, 2016)
Biohydrogen is considered the most promising biofuel as it generates only water as waste combustion. In this work, two inocula for biohydrogen production were compared, one from the treatment plant of a brewery (Inoculum A), and the other from a treatment plant of domestic residual waters (Inoculum B). In both cases, for selecting biohydrogen producing microorganisms, a pretreatment consisting of heat shock for 24 h at 104 ° C temperature, followed by crushing to reach the consistency of poder was used. The accumulated biohydrogen production was adjusted to the Gompertz model, showing that despite operating with a substrate which consisted of a 5 % glucose solution, enriched with mineral medium, stirring 15.71 rad/s at 35 °C, the latency period and productivity differed. The Inoculum A reactors generated a cumulative biohydrogen of 128.27 mL, 12 times higher than tho se inoculated with Inoculum B (9.11 mL), with productivities of 85.52 mL and 6.07 mL of H2/Lreactor/d respectively. This is attributed to the quantities of microorganisms present in the inocula compared. Biohydrogen concentration varied from 0 % to 72.42 % for the Inoculum A, and from 0 % to about 29.49 % for Inoculum B. The inoculum A strain showed high potential for biohydrogen production. Archive XML (SciELO)